EFEK MUTAGENIK EKSTRAK METANOL AMPAS BIJI JARAK (Jatropha curcas L.) SISA PENGOLAHAN BAHAN BAKAR NABATI (BIOFUEL) - Retno Wahyuningrum; Komar Ruslan Wirasutisna; Elfahmi Elfahmi; Marlia Singgih Wibowo (Majalah Obat Tradisional, 2010)
Jatropha curcas seed contains viscous oil that can be used for soap making, cosmetic and as biofuel. It contains phorbol ester that was toxic. Biofuel production of Jatropha curcas seed left seedcake from mechanical press process. For safety evaluation, mutagenicity test was carried out. The seedcake was extracted by maceration method at room temperature with methanol and the mutagenic effect was evaluated by Ames test against Salmonella typhimurium TA 1535 with or without S9 metabolic activator. Methanolic extract of Jatropha curcas seedcake had no mutagenicity effect against S. typhimurium TA 1535.